ANALYSIS OF CHEMICAL CONTENTS IN RAW MATERIAL OF RICH MINERALS SEA SALT - Fawait Afnani; Wiwit Sri Werdi Pratiwi; Makhfud Effendy; Novi Indriyawati; Vellia Yoseva (Jurnal Kimia Riset, 2022)
The mineral content of seawater is a natural raw material to produce rich mineral sea salt. Rich mineral sea salt is a consumption salt with a NaCl content of <50% used to live a low sodium diet for a healthy lifestyle. In general, traditional sea salt was produced with the multistage evaporation method to obtain a NaCl content of ≥ 94.7%, whereas the production of rich mineral sea salt uses a total evaporation method and then removes the salt flower at a certain concentration to get low sodium chlorine and contain other natural minerals. This study aims to analyze the chemical content of the raw material of rich mineral sea salt. The location of seawater used as raw material for rich mineral sea salt is Camplong District, Sampang Regency. Samples were obtained from sea level with a distance of ± 400 m from the coastline and carried out during high tide conditions. The chemical analysis of seawater samples consists of Na, Mg, Ca, K, Fe, Cl− dan SO42−. The analysis method is based on the Indonesian National Standard of environmental quality test. The results of the major mineral analysis showed that the largest mineral content of seawater was calcium (Ca2+) at 492.350±10.395 mg/L and Sodium (Na+) at 482,000±1.979 mg/L. In contrast, the smallest mineral content is iron mineral (Fe2+) of < 0.08 mg/L. These results will be used for preliminary data before producing naturally rich mineral sea salt.